Authoritarianism and Democracy in Europe, 1919-39
XII, 354 p.
Keywords: Authoritarianism and Democracy in Europe, 1919-39 offers a comprehensive analysis of the survival or breakdown of democracy in interwar Europe. The contributors explore factors such as the historical, social-structural and political-cultural backgrounds of the policies that European countries attempted to implement to counter the world economic crisis of 1929. The analysis serves as an important backdrop for the assessment of current democratic developments in former communist Europe and highlights some of the problems and risks involved in the transition process.